(untitled) (CIPEEX, 2025)
The document presents the vision of the Care Senior app, developed to encourage and facilitate elderly care at home or in nursing homes, promoting physical, emotional, and social well-being. The purpose involves creating a digital platform that provides educational content on health care, nutrition, and physical activities for the elderly, along with tools for monitoring vital signs, managing medications, and tracking health. The app also offers functionalities for scheduling family visits and encouraging interaction, aiming to bring the elderly closer to their loved ones and strengthen family bonds. Additionally, the app facilitates participation in charitable donations and volunteer activities, promoting lots of support involving not only family members but also institutions and the support network. Expected outcomes include a significant improvement in elderly’s life quality, achieved through constant monitoring and increased family and social involvement in their daily lives. The platform also seeks to optimize medical follow-ups and daily care management, ensuring greater safety and well-being. The document concludes that Care Senior will be an accessible, secure, and intuitive tool, connecting caregivers, families, and institutions in an efficient and humanized network. Thereby, the app aims to foster continuous and high-quality care, promoting closer interaction between the elderly and their families, as well as offering additional support through donations and volunteer actions, making aging healthier, more dignified, and well-supported.